The Role of Clostridioides difficile Within the One Health Framework: A Review - Sotiris Alexiou; Anastasia Diakou; Melania Kachrimanidou (Microorganisms)
Clostridioides difficile is the leading cause of antibiotic-associated diarrhea in hospitalized patients. In recent years, the incidence of C. difficile infection (CDI) has increased globally, with a notable rise in community-associated CDI (CA-CDI). The presence of the microorganism in animals, the environment, and food suggests that these sources may contribute to the spread of the infection in the community. This review applies a One Health approach, integrating human, animal, and environmental health, to provide a comprehensive strategy for understanding and managing this pathogen. Findings reveal the widespread dissemination of C. difficile in animals, the environment, and food. The predominant PCR ribotypes identified were RTs 078 and 014/020, followed by RTs 126, 001, 002, 009, 010, and 033. C. difficile strains exhibited resistance to multiple antimicrobial agents, including clindamycin, erythromycin, fluoroquinolones, cephalosporins, and tetracyclines. Discriminative typing methods, such as whole-genome sequencing, revealed clonal relationships between C. difficile strains from humans and animals, indicating either direct transmission or a common environmental source of infection. The high genetic similarity between isolates from the environment and humans indicates potential environmental contamination. Additionally, clusters of C. difficile strains found in food and humans indicate a possible foodborne transmission route. This review summarizes the current knowledge on the role of Clostridioides difficile within the One Health framework.